Relationship between physical fitness, physical activity and body mass index of adolescents. Issue 15 (10th November 2011) - Cruz, C; Sequeira, S; Gomes, H; Pinto, D; Marques, A
Abstract : The aim of this study was to examine the relationship between physical fitness (PF), physical activity (PA), and body mass index (BMI) among adolescents who attended secondary school. A total of 131 healthy students (49 boys, 82 girls) age 14 to 18 years (M=16±1) participated in the study. PA was assessed by a questionnaire based on the practice of organised and non-organised PA on a regular basis. PF level was determined by the Pacer test and allowed to label the individuals as 'not fit' or 'fit' according to the Fitnessgram. The individuals were also profiled according to their fat levels as 'not fat' or 'fat' also based on the Fitnessgram. Qui-square and t-test were performed to analyse the relationship between PF, PA, and BMI. Boys and girls were analysed separately. 66% of the boys and 38% of the girls were considered fit based on PF test. Still the majority of students did not meet the recommended 1 h/day of MVPA. The average time spent doing PA was 2.9±2.2 h/day for the boys and 1.8±1.5 h/day for the girls. The difference in PA participation levels was significant between boys and girls ( p =0.005). Almost all students were considered fit based on BMI (84% boys, 79% girls) and no differences were found between genders ( p =0.531). Although the most active boys and girls performed better on PF test, a relationship between PF and PA was not found (boys p =0.069, girls p =0.079). For both genders, students with lower BMI had better results on the PF test, however only for the boys the results were significant ( p =0.009). Additionally, there was no relationship between the practice of PA and BMI for boys ( p =0.883) and girls ( p =149). There are no relationships between PF, PA and BMI. The only exception was observed for the boys; those with lower BMI had better results on the PF test.